Предмет: Алгебра,
автор: safronovaolya98
2 cos^2 x - sin x cos x+5 sin^2 x =3
Ответы
Автор ответа:
0
2cos^2x-sinx*cosx+5sin^2x-3(sin^2x+cos^x)=0
2cos^2x-sinx*cosx+5sin^2x-3sin^2x-3cos^2x=0
-cos^2x-sinx*cosx+2sin^2x=0 все делим на cos^2x
-1+tgx+2tg^2x=0
Пусть tgx=t, тогда
2t^2+t-1=0
D=1+8=9
X1=(-1+3)/4=1/2
X2=(-1-3)/4=-1
tgx=1/2 и tgx=-1
x=-+
2cos^2x-sinx*cosx+5sin^2x-3sin^2x-3cos^2x=0
-cos^2x-sinx*cosx+2sin^2x=0 все делим на cos^2x
-1+tgx+2tg^2x=0
Пусть tgx=t, тогда
2t^2+t-1=0
D=1+8=9
X1=(-1+3)/4=1/2
X2=(-1-3)/4=-1
tgx=1/2 и tgx=-1
x=-+
Похожие вопросы
Предмет: Алгебра,
автор: temakorobey777
Предмет: Геометрия,
автор: serdarmakhmudov75
Предмет: Алгебра,
автор: bycarovarsenij
Предмет: Математика,
автор: olribalcko2014